Pyrotinib shows a potent antitumor effect on HER2-positive esophageal cancer cells by promoting HER2 proteasomal degradation : Pyrotinib induces HER2 degradation in esophageal cancer cells - Zhao, Fei; Zhu, Tienian; Zhao, Ruijing; Liu, Jiankun; Ren, Wenjun (Cellular and Molecular Biology, 2023)
Pan-HER TKIs (pyrotinib, lapatinib) are potent HER2 inhibitors, however, their anti-tumor efficacy on esophageal cancer remains to be elucidated. Using two HER2-positive esophageal cancer cell lines, we observed that both pyrotinib and lapatinib could significantly suppress the activation of HER2 and its downstream signaling. However, pyrotinib showed a potent inhibitory effect at 0.1 µM treatment relative to 1 µM of lapatinib. Moreover, treatment with pyrotinibm, but not lapatinib, markedly reduced the protein level of HER2 through enhancing HER2 ubiquitination level and proteasomal degradation. In vitro and in vivo experiments further revealed that pyrotinib effectively suppresses cancer cell invasion and migration, as well as the growth of tumors in nude mice. Overall, our results suggest that pyrotinib is a superior TKI over lapatinib in inhibiting esophageal cancer cell proliferation and tumorigenic potential, and can be chosen as a neo-adjuvant for esophageal cancer treatment.